On the status and comparison of glucose intolerance in female breast cancer patients at initial diagnosis and during chemotherapy through an oral glucose tolerance test. - Lin-jie Lu (Public Library of Science (PLoS), 2014)
Aims This study is to estimate the status and comparison of glucose intolerance in female breast cancer patients at initial diagnosis and during chemotherapy through an oral glucose tolerance test (OGTT), as well as to learn the effect of chemotherapy on the glucose metabolism of breast cancer patients. Methods All the 79 breast cancer patients at initial diagnosis, with the mean age of 53.2 years, and 96 breast cancer patients before the 5th or 6th cycle of chemotherapy, with the mean age of 51.5 years, participated in the study from December 2012 to October 2013. After an overnight fast, participants underwent OGTT test, and fasting and 2-hour glucose levels were measured to identify undiagnosed diabetes and prediabetes (i.e., impaired fasting glucose or impaired glucose tolerance) in them. Previously diagnosed diabetes among the female breast cancer patients was determined on the self-report and the medical record. Results The overall incidences of total normal glucose tolerance, prediabetes, diabetes in female breast cancer patients at initial diagnosis and during chemotherapy were 24.1% and 38.5% (p<0.05), 50.6% and 28.1% (p<0.05), and 25.3% and 33.3% (p>0.05), respectively, and the differences of normal glucose tolerance and prediabetes instead of diabetes between the two groups were statistically significant. About 84% of the total diabetes and prediabetes in the female breast cancer patients at initial diagnosis and 79.7% of those during chemotherapy need to be diagnosed with OGTT. Conclusions Breast cancer patients have high incidences of diabetes and prediabetes. After chemotherapy even with steroids, some breast cancer patients with abnormal glucose metabolism may even become normal. Isolated hyperglycemia 2 hours after glucose loading is common, and OGTT should be made for breast cancer patients at initial diagnosis and during chemotherapy.